Parental wellbeing factors In parents of children with an intellectual and developmental disability: a research portfolio - McCrohan, Fiona M. (The University of Edinburgh, 2015)
Aims: Parents of children with intellectual and developmental disabilities tend to illustrate and report higher levels of stress and lower wellbeing than parents of typically developing children. This thesis aimed to explore the aspects of this relationship between parental wellbeing and raising a child with heterogeneous intellectual and developmental disability. Firstly, the thesis aimed to review the current literature and evidence base for mindfulness-based group and individual interventions and their effect on psychological outcomes for parents of children with intellectual and developmental disabilities. Secondly, a research study aimed to explore the role of overall parental locus of control and particular sub-domains of locus of control on parent reported wellbeing. Furthermore, the role of child compliant and social behaviour, child problem behaviour, diagnostic groups, level of functioning, and demographic variables were explored. Method: A systematic review of the literature was conducted to address the first aim of this thesis. Within the research study, a single sample of parents and family carers (n = 114) completed an online anonymous survey consisting of demographic information and three self-report measures; a modified version of the Parental Locus of Control Scale, the Warwick-Edinburgh Mental Wellbeing Scale, and the Nisonger Child Behaviour Rating Form. Results: The systematic review illustrated that mindfulness-based interventions appear to have a significant effect on a number of parent psychological outcomes; such as wellbeing, stress, mental health, compassion, and mindfulness. A further four papers indicated a significant impact on child behavioural outcomes from parental mindfulness interventions. The research study indicated parental locus of control, in particular the two sub-domains of child control, and parent efficacy significantly mediated the relationship between child problem behaviour and parental wellbeing. Conclusions: There is a need to further explore the effectiveness of mindfulness interventions on parental distress and child behaviour, in particular in comparison to well-established interventions and groups. The research study results highlight the importance of parental attributions in influencing the wellbeing of parents of children with intellectual and developmental disabilities. However, it is clear from these findings that there is a complex relationship between parent cognitive attributions and broader social and societal factors. These findings may inform future practice with these families, although further research to explore these complex relationships is required.
Keywords: intellectual disability; developmental disability; parent; wellbeing; stress; coping